Physical phenomena which appear to have determined the bases and development of an harmonic sense among Bushmen, Hottentot and Bantu - Kirby, Percival R. (International Library of African Music, 1961)
A striking illustration of the use of harmonics by the Southern Bantu is afforded by an interesting flute made and played by Zulu, Swazi and, in former times, by Xhosa. It is a “seasonal” instrument, manufactured and played only at the summer solstice at the conclusion of the Festival of the First Fruits. In every respect but one this instrument, known as the umtshingo, corresponds to the oblique flute of the ancient Egyptians, the sole difference being that it lacks regular fingerholes, the opening at the end opposite to the embouchure alone fulfilling that function. If, therefore, there was ever any connection between the Zulu instrument and that of ancient Egypt, it must have been pre-Pharaonic, since all the Pharaonic oblique flutes are provided with several finger holes. I shall show how the Southern Bantu plays upon his oblique flute of reed, using for the purpose a simple brass tube open at both ends. If I blow it with its lower end open, I can produce several partials of the harmonic series; but if I blow it with the lower end closed it acts as a “stopped pipe”, and yields only the odd-numbered partials of the series. And by combining the two methods, which is precisely what the Zulu does, I obtain a pentatonic scale, based on the harmonic series, the very scale that I showed could be obtained from the Bushman’s shooting-bow.
Keywords: African Music